The double-edged sword of storytelling Performative language pedagogy with refugees, asylum seekers and migrants - Piazzoli, Erika (My University, 2021)
This article considers the ethical dimension of performative practice with refugees and migrants, positioning storytelling as a double-edged sword that can either elevate or stigmatise the storyteller. The discussion is inspired by 10 things you need to consider if you are an artist, not of the refugee and asylum seeker community, looking to work with our community, a manifesto written by Cañas, Refugee Survivor and Ex-Detainee (RISE) art director. First, the paper introduces the RISE manifesto and its significance to contemporary practice and research. Second, it discusses relevant literature, looking at the construct of aesthetic distance (Erikson, 2011), safe space as creative space (Hutton, 2008) and aesthetic form as double (Courtney, 1995) in drama. The core of the paper reports the analysis of nine interviews, conducted with professional artists, teachers and practitioners working in the context of forced migration. Data points to the interconnectedness between participants and facilitator, in terms of self-expression, creativity, vulnerability and agency. In this regard, the authors reframe vulnerability as an active, creative, liminal space essential to foster an ethical imagination. This kind of creative vulnerability, key to practitioners’ ethical imagination in performative work, can act as a segue into the symbolic, metaphorical mode of drama.
PUBLISHED
Keywords: Creative Arts Practice; Identities in Transformation; forced migration; Education; Relationships